Switch of Bacteria Community Under Oxygen Depletion in Sediment of Bohai Sea - Guo, Xiaoxiao; Song, Guisheng; Li, Yanying; Zhao, Liang; Wang, Jing (Frontiers in Marine Science, 2022)
Regular oxygen depletion is occurring every summer in the depression area of the Bohai Sea. The community structure and potential functions of microbes in expanding marine hypoxic area are of great importance due to their roles in biogeochemical cycling. In this study, the diversity and distribution of bacteria based on 16S rRNA gene in sediment along an inshore-offshore transect across the oxygen-depletion area in the Bohai Sea was investigated in June, July and August of 2018 by employing high-throughput sequencing. Results revealed that the bacteria community was dominated by Proteobacteria (42.67%), Actinobacteria (14.13%), Chloroflexi (13.02%), Acidobacteria (8.01%) and Bacteroidetes (6.30%). During oxygen depletion, the bacteria community from inshore site A3 subjected to dramatic variation from June to August, but the composition tended to be stable in sites from depression area along the transect. Distinct switch of bacteria from aerobic to anaerobic group was observed when the DO concentration < 4.2 mg/L, typically represented by dominance of Anaerolineaceae in August sample. Further, KEGG prediction by PICRUSt confirmed the variations by showing significant difference in functional pathways, especially the nitrogen metabolisms, before and after DO depletion (p < 0.05). These variations could be influenced by depth, NO2- concentration and DO availability based on RDA analysis. The details in diversity and composition of bacteria under continually observation provides insights into both instant and long-term response of bacteria community to oxygen depletion, and the distinct functional switch under this process expands our knowledge on the metabolic character of bacteria in worldwide hypoxia areas.